2013
DOI: 10.4067/s0034-98872013001100011
|View full text |Cite
|
Sign up to set email alerts
|

La hipótesis de Pedersen no es suficiente: Otros nutrientes además de la glucosaexplicarían la macrosomía fetal enpacientes diabéticas gestacionales consobrepeso y buen control glicémico

Abstract: La hipótesis de Pedersen no es suficiente:Otros nutrientes además de la glucosa explicarían la macrosomía fetal en pacientes diabéticas gestacionales con sobrepeso y buen control glicémico

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…This conclusion was reached on the basis of a lower free fatty acids AUC for the HC/LF(CHOICE) diet (19%, P <0.01). Other studies have shown similar results, suggesting that higher levels of carbohydrate with concomitant lower levels of fat produce favorable outcomes ( 3 , 5 , 8 , 9 , 12 , 15 , 23 ).…”
mentioning
confidence: 52%
“…This conclusion was reached on the basis of a lower free fatty acids AUC for the HC/LF(CHOICE) diet (19%, P <0.01). Other studies have shown similar results, suggesting that higher levels of carbohydrate with concomitant lower levels of fat produce favorable outcomes ( 3 , 5 , 8 , 9 , 12 , 15 , 23 ).…”
mentioning
confidence: 52%
“…In pathological pregnancies, complications with diabetes, hypertension, proteinuria or even renal failure are often reported. [25][26][27][28][29][30][31] Although couples of theories are suggested to explain the cross-talk between the enlarged uterus and other abdominal organs, a simple and more straightforward hypothesis Notes: The alterations of large number of chemicals, including insulin, lipid related components, renin, angiotensin, and sex hormones, may simply reflect pathological changes of the abdominal organs in responding to increased pressure. Although one may argue that these chemicals are the direct causes of metabolic syndrome, this is highly unlikely due to the large number of various chemicals involved.…”
Section: Increased Abdominal Pressure Responsible For Mutual Relationmentioning
confidence: 98%
“…El primer caso de diabetes en el embarazo fue descrito por el doctor Bennewitz en 1824, se trató de una gestante que desarrollo DM presentando síntomas de polidipsia y poliuria, además una glucosuria de 125 g/L que desaparecieron luego del parto, (28) la presencia de varios casos posteriores en Estados Unidos y Reino Unido señaló una alta tasa de mortalidad perinatal en mujeres con diabetes en el embarazo. En 1909 Williams dio a conocer los posibles primeros criterios de diagnóstico por lo que propuso umbrales fisiopatológicos y fisiológicos para una glucosuria transitoria en las gestantes.…”
Section: Antecedentesunclassified